A New Clinical Classification Of Common Facial Clefts - Prakash C. Sood; N. N. Khanna (Indian Journal of Plastic Surgery)
A new clinically orientated classification of common facial clefts with an outline of deformities is being presented. This may advance the field of research and help in giving a better deal for the management of these malformations.